"Aliens" vs. Catalogers: Bias in the Library of Congress Subject Heading. Issue 4 (2nd October 2019) - Lo, Grace
Abstract: Aliens: It is the subject of conspiracy theories and nightmares, the name of a blockbuster science fiction/horror movie franchise, and also how the de facto national library of the United States refers to "persons who are not citizens of the country in which they reside." In 2016, the Library of Congress announced that it would reconsider the usage of "Aliens" and its related terms in the Library of Congress Subject Headings, following a student-led movement to change the pejorative term "Illegal Aliens." Yet, three years on, these terms remain in the LCSH. Using the "Illegal Aliens" controversy as a case study, this article explores how the LCSH works, its role in research, and its vulnerabilities to bias, and offers proposals for how librarians can help improve the situation.